Redesign Corporate Identity Pada PT. Sentral Mega Konsultan - Priki Adimarta; Meyti Eka Apriyani (JURNAL INTEGRASI, 2014)
PT Sentral Mega Konsultan standing end of 2012 and is relatively new in the field of IT consulting. This company has a lot of cooperation to deal with various government and private agencies in the province of Kepulauan Riau. PT Sentral Mega Konsultan has had a corporate identity like other companies. However, the identity of the company could never used for daily operations of the company, especially for the purposes of promotion that have not been done. The identity of a company logo that has not been implemented into the medium which is used by a company for promotional activities and even in the application of the logo looks less attractive tends to monotony. So far clients are coming, get to know the company is only through word of mouth information. There was never any promotional efforts undertaken by the company, however with the advent of more and more companies in the same field, the company felt the need to do something to maintain the existence of companies one of which is the promotion to introduce the PT Sentral Mega Konsultan to the general public. Of the problems that come necessary to redesign the visual identity of the company which will be implemented in a variety of media promotion.